2020
DOI: 10.1021/acscatal.0c03014
|View full text |Cite
|
Sign up to set email alerts
|

Cu(I)-Catalyzed Enantioselective [5 + 1] Cycloaddition of N-Aromatic Compounds and Alkynes via Chelating-Assisted 1,2-Dearomative Addition

Abstract: Copper-catalyzed [5 + 1] cycloadditions of N-aromatic zwitterions have been accomplished by chelation-assisted 1,2-dearomative addition of electron-deficient terminal alkynes. The unique modular skeleton of pyrazino­[1,2-a]­quinoline could be obtained from the regio- and stereoselective cascade annulation process, which was supported by computational studies. Further, an asymmetric variant of the developed strategy has been successfully extended for enabling access to optically enriched six-member cyclic syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 94 publications
0
15
0
Order By: Relevance
“…Based on such a chelation strategy, our group developed [5 + 1] cycloadditions of N‐quinolinium zwitterions via 1,2‐dearomative addition of copper acetylides (Scheme 1(b)). 7 Although studying the feature of N‐aromatic zwitterions, we found that the twisted architectures of N‐aromatic zwitterions were sterically advantageous for chelation with metal species 8 . Although we have mainly focused on the development of cycloadditions of N‐aromatic zwitterions, 9 the development of regioselective dearomatization reactions for easy access to piperidine derivatives has also been of interest.…”
Section: Figurementioning
confidence: 99%
“…Based on such a chelation strategy, our group developed [5 + 1] cycloadditions of N‐quinolinium zwitterions via 1,2‐dearomative addition of copper acetylides (Scheme 1(b)). 7 Although studying the feature of N‐aromatic zwitterions, we found that the twisted architectures of N‐aromatic zwitterions were sterically advantageous for chelation with metal species 8 . Although we have mainly focused on the development of cycloadditions of N‐aromatic zwitterions, 9 the development of regioselective dearomatization reactions for easy access to piperidine derivatives has also been of interest.…”
Section: Figurementioning
confidence: 99%
“…In the recent years, most of the new dearomatization reactions have consisted in cycloaddition (CA) reactions or formal CA. This includes [2+2]‐, [9] [3+2]‐, [10] [3+3]‐, [11] [4+2]‐, [12] [5+1]‐, [13] and [4+3]‐CA [14] . In most of the cases theses CA reactions concern indole derivatives as substrates.…”
Section: Methodsmentioning
confidence: 99%
“…In 2020, Baik, Yoo and co-workers devised a copper-catalyzed dearomative [5+1] cycloaddition of quinolinium zwitterionic tosylate 91 with terminal alkynes 92 to afford pyrazino[1,2- a ]quinoline skeleton 93 . 62 The proposed mechanism is shown in Scheme 25 . The diisopropylethylamine (DIPEA)-promoted deprotonation produces nucleophilic copper acetylide intermediate A , which undergoes the dearomative addition to the quinolinium zwitterions 91 .…”
Section: Annulation Involving Quinolinium Zwitter­ionic Tosylatesmentioning
confidence: 99%